Cardiac phenotype in mouse models of systemic autoimmunity - Chandan Sanghera; Lok Man Wong; Mona Panahi; Amalia Sintou; Muneer Hasham; Susanne Sattler (The Company of Biologists, 2019)
Patients suffering from systemic autoimmune diseases are at significant risk of cardiovascular complications. This can be due to systemically increased levels of inflammation leading to accelerated atherosclerosis, or due to direct damage to the tissues and cells of the heart. Cardiac complications include an increased risk of myocardial infarction, myocarditis and dilated cardiomyopathy, valve disease, endothelial dysfunction, excessive fibrosis, and bona fide autoimmune-mediated tissue damage by autoantibodies or auto-reactive cells. There is, however, still a considerable need to better understand how to diagnose and treat cardiac complications in autoimmune patients. A range of inducible and spontaneous mouse models of systemic autoimmune diseases is available for mechanistic and therapeutic studies. For this Review, we systematically collated information on the cardiac phenotype in the most common inducible, spontaneous and engineered mouse models of systemic lupus erythematosus, rheumatoid arthritis and systemic sclerosis. We also highlight selected lesser-known models of interest to provide researchers with a decision framework to choose the most suitable model for their study of heart involvement in systemic autoimmunity.